Electrocution Mortality of Imperial Eagle on Medium Voltage Power Lines in Slovakia – Causes and Solutions - Marek Gális; Roman Slobodník; Jozef Chavko (Пернатые хищники и их охрана)
Medium-voltage power lines are one of the most important mortality factors of raptors in Slovakia. Among the frequent victims of electrocution are also rare species, such as the Imperial Eagle (Aquila heliaca). Many of the breeding pairs have gradually relocated from the foothills to nearby agrocenoses, with a higher risk of possible electrocution, as they often use the poles for resting. In Slovakia the problem of electrocution has been the focus for mitigation measures since 1991. Especially the LIFE Energy project (implemented in 2014–2019) brought new insight into this topic, as systematic monitoring of almost 61,000 medium voltage poles was carried out in 2014–2016. Electrocution was defined as the main mortality factor of cadavers found.